Epidemiology of ocular pathology in domestic animals: insights from a 20-year retrospective study - Garcia, Jamile Macedo; Rogerio, Guilherme da Silva; Rossatto-Júnior, Carlos Alberto; Bezerra, Lorena Santos; Schulz, Érica Thurow; de Morais, Raphael Assis Leandro; Dagli, Maria Lucia Zaidan (Frontiers in Veterinary Science, 2026)
Ocular pathology holds significant importance in veterinary medicine, providing essential insights into diagnosing and characterizing eye and periocular diseases in animals. This retrospective study aimed to identify and characterize the most frequent lesions affecting the eyes and surrounding structures in domestic animals. A total of 375 ocular and periocular samples, retrieved from the Animal Pathology Service of the Veterinary Hospital at the School of Veterinary Medicine and Animal Science of the University of São Paulo, São Paulo, Brazil, from 2003 to 2022, were analyzed. Most samples came from dogs (64%), followed by cats (15.20%), and horses (12.27%). Neoplastic lesions were the most common (80.53%), especially squamous cell carcinoma (SCC) (20.26%), followed by inflammatory (10.4%) and other lesion types (e.g., hyperplastic, cystic, infectious). Eyelids were the most frequently affected anatomical site. SCC was particularly frequent in the third eyelid of cattle and in the eyelids and conjunctiva of cats and horses. A statistically significant difference was observed between brachycephalic and non-brachycephalic dog breeds, with the former showing fewer neoplastic lesions. Clinical suspicion matched the histopathological diagnosis in 84.1% of cases, although the agreement was moderate according to the Kappa coefficient. Unique findings included a high incidence of meibomian adenocarcinomas and ocular melanoma in dogs, and conjunctival SCC in cats. These results underscore the importance of histopathological evaluation for accurate diagnosis and recommend increased sample submissions to support pathologist training and improve diagnostic accuracy.